Research on Viewpoint Planning Method for Multi-view Image 3D Reconstruction - Shi, Yun; Zhu, Yanyan (Manufacturing Technology Journal, 2023)
A model-based viewpoint planning and filtering method is proposed to determine the position and pose of viewpoints in 3D reconstruction of multi-view images. The method first determines the necessary parameters to control the camera position and attitude. Second, the mathematical error model is developed and combined with stereo overlap to guide viewpoint selection. According to the shooting distance, a dense candidate view area is then established, the subview collection is screened, & a view supplement scheme is proposed for the area where the candidate view cannot be shot, improving the integrity of the resulting data. Experimental results demonstrate that our viewpoint planning method has high shooting coverage & highly accurate 3D reconstruction.
Keywords: Multi-view; 3D reconstruction; Aerial-photography; View Planning